2012
DOI: 10.1007/s11948-011-9346-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Engagement with Ethics Between an Engineering and a Business Program

Abstract: Increasing university students' engagement with ethics is becoming a prominent call to action for higher education institutions, particularly professional schools like business and engineering. This paper provides an examination of student attitudes regarding ethics and their perceptions of ethics coverage in the curriculum at one institution. A particular focus is the comparison between results in the business college, which has incorporated ethics in the curriculum and has been involved in ethics education f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Many professional programs, like business, have been placing increasing emphasis on ethics, over the past decade or so (Bebeau 2002;Culver et al 2013). This has been motivated in part by a number of high-profile scandals involving major corporations and senior executives, but also by a growing realization of the need for professionals who can adapt to new pressures (e.g., those brought on by technology) while upholding values like responsibility, respect, trustworthiness, honesty, and fairness (Culver et al 2013).…”
Section: Ethics Education Within the Professions: A Business School Ementioning
confidence: 99%
“…Many professional programs, like business, have been placing increasing emphasis on ethics, over the past decade or so (Bebeau 2002;Culver et al 2013). This has been motivated in part by a number of high-profile scandals involving major corporations and senior executives, but also by a growing realization of the need for professionals who can adapt to new pressures (e.g., those brought on by technology) while upholding values like responsibility, respect, trustworthiness, honesty, and fairness (Culver et al 2013).…”
Section: Ethics Education Within the Professions: A Business School Ementioning
confidence: 99%
“…Previous work by Culver et al (2013) that compared business students and engineering students for their understanding of professional ethics reported that engineering students showed relatively narrow and rigid views. The discrepancy was distinct in the issues of global difference, social and cultural implications, and the relationship between professional and personal ethics.…”
Section: Sdp$teammentioning
confidence: 99%
“…Therefore, it is likely that Page 26.728.11 students' explicit understanding is strongly related to what they learn in formal engineering education. Engineering students reportedly feel that they do not receive satisfactory ethics instruction through their curriculum (Culver et al, 2013). Cech (2014) reports a "culture of disengagement" in engineering education that may explain this shared, narrow explicit understanding.…”
Section: Sdp$teammentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the direct involvement of engineers in developing these technologies, there is a growing call for ethics training across engineering disciplines from accreditation boards, professional societies, and societal views for training in ethics across engineering disciplines 2,31,54 . However, many engineering colleges do not effectively prepare students to reason through the ethical challenges posed by "grey-area" ethical issues such as those stemming from new and emerging technologies 15 , nor do they demonstrate effective development of the higher levels of ethical reasoning necessary for such analysis. Furthermore, evidence indicates that while engineering students experience a wide range of ethics pedagogy, they still have lower levels of ethical reasoning than their peers in other disciplines 22 , although some studies suggest that these differences may be accounted for by other variables, such as gender 48 .…”
Section: Introductionmentioning
confidence: 99%